The Effect of Islamic Financial Literacy on Consumptive Behavior of Students of Islamic Economics Study Program IAIN Takengon - Rahma Nurzianti (Universitas Gorontalo, 2022)
Islamic financial literacy and consumptive behavior are consumer activities in believing, knowing and skills in managing Islamic finance in spending a product with a wise attitude. The purpose of this study was to determine the effect of Islamic financial literacy on the consumptive behavior of students of the Islamic Economics study program at IAIN Takengon. This study uses quantitative methods with the population and samples are students of the Islamic Economics study program. The analysis used in this study is a simple linear regression analysis with testing the validity and reliability of the primary data. The results show that Islamic financial literacy has a negative relationship and has no effect on student consumption behavior, which means that the higher the level of Islamic financial literacy causes a decrease in student consumptive behavior.